Stepped‐up surveillance for early detection of Anoplophora chinensis in a nursery district1. (August 2015) - Ciampitti, M.; Cavagna, B.; Bianchi, A.; Cappa, V.; Asti, S.; Fumagalli, A.
<x xml:space="preserve">Abstract</x> The Plant Protection Service of Lombardy Region (Italy) has been working to control Anoplophora chinensis for many years. A specific plan was developed by the Plant Protection Service in 2011 to implement stepped‐up surveillance for early detection of this pest in the most important nursery area in the region. The Canneto sull'Oglio district area hosts the highest concentration of commercial nurseries in Lombardy. The nurseries specialize in the cultivation of full‐size deciduous ornamental trees. The reinforced surveillance plan includes the following steps: planning, inspection of the urban green spaces, surveillance in rural areas and surveillance of identified sources of risk. A new procedure was defined for the enhanced territorial surveillance, as there were no established guidelines to follow. Two buffer zones were delineated, with a 2 km radius and a 500 m radius around all the areas dedicated to nursery cultivation, and a grid of 500 × 500 m was superimposed on it. Between one and four inspection points were defined for each cell, depending on the risk to plant health, and more than 3450 inspection points were identified, corresponding to 11 233 potential host plants that were to be inspected. In addition, the fields of 16 nurseries classified as high risk sources were inspected as well as the potential hosts in the buffer zone of 100 m radius around them. The annual cost of the surveillance is 30 000 EUR, which corresponds to about 0.025% of the annual production value of the nurseries in this district.